Dynamic strength measurement of aluminum under magnetically driven ramp wave pressure-shear loading. (February 2017) - Luo, B.Q.; Chen, X.M.; Wang, G.J.; Tan, F.L.; Chen, G.H.; Zhao, J.H.; Sun, C.W.
Highlights: A technique of magnetically applied pressure-shear (MAPS) was developed and established for directly measuring dynamic strength of materials under ramp wave loading on compact pulsed power generator CQ-4 combining a 10 T quasi-static magnetic field device by us. The working principle of MAPS was proved and validated in theoretical analyses and simulated models. Also a multi-point Photonic Doppler Velocimetry (PDV) was developed to measure transverse and longitudinal velocities in experiments. The strength of two different alumina was finally measured by means of MAPS, the results of which showed that MAPS is a good tool for measurements of material strength. Abstract: The strength of a material at high pressure is an important physical parameter in shock physics and material science. In this work, a magnetically applied pressure shear loading technique, combining magnetically driven longitudinal and shear waves, was developed to measure material strength in high pressure and high strain rate experiments. Using theoretical and numerical analysis, we obtained a relationship between the deviatoric stresses and the yield stress, and demonstrated the strength calculation method. Experiments were then conducted on pulsed power generator CQ-4, with a newly established quasi-static magnetic field generator to produce shear stresses, and transverse velocity measurement techniques to determine the results. The experiments measured the strength of polished and cold rolled aluminum at high pressure. The strength of polished aluminum agreed well with previous data measured using self-consistent methods under ramp wave loading. The strength of cold rolled aluminum was larger due to differences of initial plastic deformation. Meanwhile, the strength of both polished and cold rolled aluminum increased with pressure.